The Effect Of Using Duolingo On English Writing For EFL University Students - Ratu Shania Nazjwa Salsabilla; Khairunnisa; Resti Amelinda Iranti Lukman; Abdul Syahid (CV. Ulil Albab Corp, 2024)
This study aims to measure the effectiveness of using the Duolingo application in improving English writing skills among EFL students at IAIN Palangka Raya. The research adopts a quantitative approach with saturated sampling techniques and data collection through questionnaires involving 20 respondents. Data analysis was conducted using Jamovi. The findings indicate that although there is an average difference between Duolingo users and non-users, the difference is not statistically significant across various measured aspects, such as writing confidence, skill improvement, and satisfaction with learning outcomes. These findings suggest that while Duolingo has potential as a learning support tool, its impact on writing skills remains limited. Therefore, the study recommends integrating the application with traditional teaching methods for more optimal results